Physical Distance and Cooperativeness Towards Strangers - Leonie Kühl; Nora Szech (Center for Economic Studies and ifo Institute (CESifo), 2017)
Cooperativeness among genetically unrelated humans remains a major puzzle in the social sciences. We explore the causal impact of physical distance on willingness to help. In a field setting, participants decide about supporting local refugees at the dispense of money to themselves. We vary physical distance only, and keep other factors such as cultural distance fixed. The data shows that an increase in local physical distance decreases willingness to donate. A laboratory experiment confirms this finding. We further explore the causal roles of exposure (in the field) and of larger distances (in the lab) with a total of 475 participants.
Keywords: C91; C93; D64; 330; cooperativeness; physical distance; strangers; morally relevant behavior; local neighborhoods